Reason and Communication: Jürgen Habermas’s Legacy for Media and Communication Studies - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Bridging the Dual Nature: How Integrated Explanations Enhance Understanding of Technical Artifacts - Terfloth, Lutz; Buhl, Heike M.; Lohmer, Vivien; Schaffer, Michael; Kern, Frederike; Schulte, Carsten

Retrospective video recall for analyzing cognitive processes in naturalistic explanations - Lazarov, Stefan Teodorov; Schaffer, Michael; Gladow, Viviane; Buschmeier, Hendrik; Buhl, Heike M.; Grimminger, Angela
In this paper, we discuss the application of retrospective video recall for the assessment of cognitive processes in explanatory interactions, such as understanding and mental models. Our purpose is to reflect on the benefits and limitations of video recall compared to another self-report method, ‘thinking-aloud’. To do so, we reveal empirical results from the application of video recall in three interdisciplinary research projects that applied the method for the qualitative and quantitative assessment of cognitive and behavioral phenomena in everyday explanations. In all three projects, video recall was applied as a post-hoc procedure following the recording of dyadic face-to-face explanations of board games. The design of the video recall procedure differed between individual projects because they pursued different research objectives – that is the investigation of (1) an interlocutor's multimodal signals of understanding, (2) the change in assumptions about an interlocutor's dispositional and situational knowledge, and (3) the differentiated assessment of an interlocutor's developing understanding of domain knowledge aspects by distinguishing between mechanistic and functional explanatory stances. By discussing the benefits and the limitations of each procedure, this article provides critical reflections on video recall as a versatile research method applied for the analysis of human multimodal behavior in interaction and cognitive processing.

Aggregation Processes in Customer Rating Systems - Insights from an Economic Decision Experiment - van Straaten, Dirk; Mir Djawadi, Behnud; Melnikov, Vitalik; Hüllermeier, Eyke; Fahr, René (SSRN Electronic Journal)
The aggregation of rating metrics in reputation systems is crucial for mitigating information overload by condensing customer rating distributions into singular valence scores. While platforms typically employ technical aggregation functions, such as the arithmetic mean to capture product quality, it remains unclear whether these functions align with customers' innate aggregation patterns. To address this knowledge gap, we designed a controlled economic decision experiment to elicit customers' aggregation principles by analyzing their product ranking decisions and contrasting these with various reference functions. Our findings indicate that, on average, customers aggregate rating information in accordance with the arithmetic mean. However, a granular analysis at the individual level reveals significant heterogeneity in aggregation behavior, with a substantial cluster exhibiting binary patterns that focus equally on negative (1-2 star) and positive (4-5 star) ratings. Additional clusters concentrate on negative feedback, particularly 1-star ratings or 1-2 star ratings collectively. Notably, these inherent aggregation patterns exhibit stability across variations in numerical information presentation and are not significantly influenced by individual characteristics, such as online shopping experience, risk attitudes, or demographics. These findings suggest that while the arithmetic mean captures average consumer behavior, platforms could benefit from offering customizable aggregation options to better cater to diverse user preferences for processing rating distributions. By doing so, platforms can enhance the effectiveness of their reputation systems and improve the overall quality of decision-making for consumers.

Migration and Long-Term Demographic Change: Can We Control the Numbers? - Abbink, Klaus; Mir Djawadi, Behnud (SSRN Electronic Journal)
In many Western societies, mass immigration has been one of the most divisive policy issues in recent years. Seemingly moderate inflows of migrants can have substantial demographic consequences in the long run, due to (1) higher fertility of the migrant population, (2) its younger age distribution, and (3) the possibility of family reunification. Yet, demography hardly appears in the policy debate, even in media outlets that are critical of mass immigration. This may indicate that the mechanics of population dynamics are not widely understood. We design a laboratory experiment in which we confront subjects with 30 different migration scenarios. Subjects have to decide when to stop a given inflow of migrants to achieve a target share of migrants after 60 years. In line with all our pre-registered hypotheses, in scenarios that contain elements of usual mass immigration the growth of the migrant population is systematically underestimated. This bias is even stronger in scenarios that closely resemble the German situation since the opening of the borders during the 2015 refugee crisis.

Dishonesty of Parents and Children – Evidence from a Field Experiment - Mir Djawadi, Behnud (SSRN Electronic Journal)

Decentring the governance of AI in the military: a focus on the postcolonial subject - Bhila, Ishmael (AI and Ethics)
The governance of emerging technologies with increased autonomy in the military has become a topical issue in recent years, especially considering the rapid advances in artificial intelligence and related innovations in computer science. Despite this hype, the postcolonial subject’s position has been seen as secondary, often associated with victimhood or obscurity. By shifting the narrative to highlight the postcolonial subject’s agency—not only in providing real-world examples of artificial intelligence use in the military but also in knowledge creation and shaping the discourse on governance within the international, this paper contributes to an area of research that is often overlooked. The paper unpacks the norm-making efforts of postcolonial subjects regarding emerging military technologies. In doing this, the paper aims to advance postcolonial theory by showing how the dynamics of governing emerging military technologies intertwine with postcolonial subjectivity and to broaden the academic discussion on the governance of emerging military technologies and algorithmic violence, which has so far been dominated by Western or universalistic discourse.

Praxisschock oder Kohärenz? – Retrospektive Einschätzungen von Berufseinsteiger*innen zu den Phasen der Lehrkräftebildung - Homt, Martina

Behind the Mask: Investigating the Influence of Pseudonymity on Polarization Dynamics in Social Virtual Reality - Tölle, Laura; Rose, Robert; Trier, Matthias

Social Support and Emotional Expression – Exploring Online Community Polarization Dynamics: The Case of Borussia Dortmund - Tölle, Laura; Trier, Matthias

Content Themes and Self-Presentation of Virtual Influencers - Tölle, Laura; Rehmer, Torben; Ruppel, Fynn; Müller, Johann; Trier, Matthias

The Schrödinger equation with fractional Laplacian on hyperbolic spaces and homogeneous trees - Palmirotta, Guendalina; Sire, Yannick; Anker, Jean-Philippe (Journal of Differential Equations)
We investigate dispersive and Strichartz estimates for the Schrödinger equation involving the fractional Laplacian in real hyperbolic spaces and their discrete analogues, homogeneous trees. Due to the Knapp phenomenon, the Strichartz estimates on Euclidean spaces for the fractional Laplacian exhibit loss of derivatives. A similar phenomenon appears on real hyperbolic spaces. However, such a loss disappears on homogeneous trees, due to the triviality of the estimates for small times.
Keywords: Schrödinger equation; Fractional Laplacian; Dispersive estimates; Strichartz estimates; Real hyperbolic spaces; Homogeneous trees

Patterson-Sullivan distributions of finite regular graphs - Arends, Christian; Palmirotta, Guendalina (arXiv:2603.09779)
On finite regular graphs, we construct Patterson-Sullivan distributions associated with eigenfunctions of the discrete Laplace operator via their boundary values on the phase space. These distributions are closely related to Wigner distributions defined via a pseudo-differential calculus on graphs, which appear naturally in the study of quantum chaos. Using a pairing formula, we prove that Patterson-Sullivan distributions are also related to invariant Ruelle distributions arising from the transfer operator of the geodesic flow on the shift space. Both relationships provide discrete analogues of results for compact hyperbolic surfaces obtained by Anantharaman-Zelditch and by Guillarmou-Hilgert-Weich.

Predictors of primary school students’ prosocial behaviour toward peers with social-emotional difficulties in inclusive education: Insights from the Theory of Planned Behaviour. Individual Paper Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. (accepted) - Löper, Marwin Felix; Knickenberg, Margarita; Hellmich, Frank

Social and emotional competencies for cooperative learning in inclusive primary education: A project overview. Poster Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. (accepted) - Casamassima, Gianna; Funk, Michael; Knickenberg, Margarita; Löper, Marwin Felix; Grosche, M.; Zimmer, L.; Grüßing, M.; Wess, N.; Hellmich, Frank

Teachers’ conceptualizations of social-emotional competencies in cooperative learning: Insights from inclusive primary school classrooms. Individual Paper Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. (accepted) - Knickenberg, Margarita; Funk, Michael; Casamassima, Gianna; Löper, Marwin Felix; Hellmich, Frank

Zum Umgang mit persönlicher Betroffenheit im Pädagogikunterricht. Perspektiven und Handlungsstrategien von Pädagogiklehrkräften - und für sie - Hanke, Jule Lara; Schwarz, Lea Marie; Engemann, Mario (Zeitschrift PädagogikUNTERRICHT)

Cells on Autopilot: Adaptive Cell (Re)Selection via Reinforcement Learning - Illian, Marvin; Khalili, Ramin; Rocha, Antonio A. de A.; Wang, Lin (arXiv:2601.04083)
The widespread deployment of 5G networks, together with the coexistence of 4G/LTE networks, provides mobile devices a diverse set of candidate cells to connect to. However, associating mobile devices to cells to maximize overall network performance, a.k.a. cell (re)selection, remains a key challenge for mobile operators. Today, cell (re)selection parameters are typically configured manually based on operator experience and rarely adapted to dynamic network conditions. In this work, we ask: Can an agent automatically learn and adapt cell (re)selection parameters to consistently improve network performance? We present a reinforcement learning (RL)-based framework called CellPilot that adaptively tunes cell (re)selection parameters by learning spatiotemporal patterns of mobile network dynamics. Our study with real-world data demonstrates that even a lightweight RL agent can outperform conventional heuristic reconfigurations by up to 167%, while generalizing effectively across different network scenarios. These results indicate that data-driven approaches can significantly improve cell (re)selection configurations and enhance mobile network performance.

Breaking the Ice: Analyzing Cold Start Latency in vLLM - Shaaban KabakiboKabakibo, Huzaifa; Trivedi, Animesh; Wang, Lin (The 9th Annual Conference on Machine Learning and Systems (MLSys))

Before the First Token: Benchmarking Data Preprocessing in Vision-Language Models - Zohdi, Sepideh; Wang, Lin (The 6th Workshop on Machine Learning and Systems (EuroMLSys))